Highly efficient povidone-phosphotungstic acid catalyst for the tandem acetalization of aldehydes to bis- and tris(indolyl)methanes - Kamble, Sumit B.; Swami, Rameshwar K.; Sakate, Sachin S.; Rode, Chandrashekhar V. (ChemPlusChem, 2013)
A novel, nonleachable hybrid of heteropoly acid and polyvinylpyrrolidone (or povidone) catalyzes the acetalization of aldehydes in methanol at room temperature followed by reaction with indole to give bis(indolyl)methanes (BIMs) and tris(indolyl)methanes (TIMs) in quantitative yields (90-97%). The catalyst was shown by pyridine FTIR spectroscopy to possess BrOnsted acidity, and the hybrid formation was confirmed by XRD and (PNMR)-P-31 studies. Friedel-Crafts alkylation of indole as well as the tandem synthesis of BIMs and TIMs were established with several types of carbonyl and indole substrates to give the corresponding products quantitatively. The catalyst was recycled efficiently for three successive runs without losing its original activity.
Keywords: acetals; Acidity; aldehydes; heterogeneous catalysis; heteropoly acids

Highly efficient triphenyl(3-sulfopropyl)phosphonium functionalized phosphotungstic acid on silica as a solid acid catalyst for selective mono-allylation of acetals - Kamble, Sumit B.; Shinde, Suhas H.; Rode, Chandrashekhar V. (Catalysis Science & Technology, 2015)
Silica supported phosphotungstic acid functionalized with triphenyl(3-sulfopropyl)phosphonium (PW-Si/TPSP) was developed as a solid acid catalyst for C-C bond formation via Hosomi-Sakurai allylation of acetals. Functionalization of PW as well as its binding to silica was confirmed by solid state P-31-NMR and Si-29-NMR, respectively. Among the various catalysts prepared, the 30% PW loaded (30PW-Si/TPSP) catalyst gave an excellent yield of homoallyl ethers (HAEs) via selective mono-allylation of acetals with allyltrimethylsilane. A plausible reaction pathway has also been proposed in which the strong Bronsted acid sites of 30PW-Si/TPSP play an important role in activating the acetals to form the corresponding oxonium cations. The versatility of our catalyst was demonstrated for the allylation of a wide variety of acetals while its stability was established in five successful recycling runs.